PWE-161 Preventing Post-ERCP Pancreatitis (PEP): The Role of Prophylactic Pancreatic Duct Stenting In The Rectal NSAID era. (17th August 2016) - Bekkali, N; Thomas, T; Murray, S; Joshi, D; Johnson, G; Chapman, M; Pereira, S; Webster, G
Abstract : Introduction: Post ERCP pancreatitis (PEP) is an important complication. Rectal NSAIDs at ERCP is the standard of care to reduce the risk. Pancreatic duct (PD) stenting also reduces the risk of PEP in high risk patients, but placement can be technically challenging. Failed PD stenting carries reported PEP rates of at least 35%. We aimed to assess whether prophylactic pancreatic stenting is still justified in the current rectal NSAID era. Methods: Between January 2013 and June 2015, we retrospectively evaluated the use of PD stents in a UK tertiary referral centre. Rectal NSAIDs were used universally for all cases post-ERCP, except in those contraindicated to NSAIDs. Prophylactic PD stenting (unflanged 5Fr 5–7 cm single pigtail stents, Cook Medical) was attempted in predicted high risk PEP cases. Indications for therapeutic PD stents included patients with chronic pancreatitis. Data was collected from our prospective database, completed following each ERCP. Follow-up information was reviewed through electronic records and telephone enquiry. Results: 1633 ERCPs were performed during the study period. Pancreatic stenting was attempted in 324 cases (20%); successful placement was achieved in 307 cases (95%). Prophylactic PD stenting failed in 12 cases, one case developed PEP (1/12 = 8%). This patient had sphincter of Oddi dysfunction (SOD) and a contraindication to NSAIDs. 65% (201/307), of successfully placed pancreatic stents were inserted prophylactically, in whom 9% (18/201) developed PEP. PEP occurred in 1.4% (18/1309) of cases who did not undergo attempted PD stenting. The relative risk of PEP was 8.4 (p = 0.04) in the stented group. Conclusion: PEP rates in failed PD stenting were low (8%) compared to past studies, and comparable to PEP rates in successful prophylactic PD stenting. This suggests a protective role of rectal NSAIDs, as previously shown by Choksi et al. 1 The higher rate of PEP in the PD stenting/attempted stenting group, compared to the unstented group, likely reflects the higher perceived risk of PEP in the PD stenting group. The low rate of recorded PEP in the unstented group may, in part, be due to under-reporting. Our data suggests that increased rates of PEP continue to be seen in perceived high risk cases, even in a universal NSAID use setting. The overall risk appears lower than in the pre-NSAID era, and in our series a lack of difference in the PEP rate between successful and failed PD stenting suggests there is less need for prophylactic PD stenting in the NSAID era. Reference: 1 Choksi, et al . The risk of post-ERCP pancreatitis and the protective effect of rectal indomethacin in cases of attempted but unsuccessful prophylactic pancreatic stent placement Gastrointest Endosc 2015;81 (1):150–155. Disclosure of Interest: None Declared